Survey on LMS Moodle for Adaptive Online Learning Design - Linawati, Linawati; Wirastuti, NMAE Dewi; Sukadarmika, Gede (Journal of Electrical, Electronics and Informatics; Vol 1 No 1 (2017): JEEI (February 2017), 2017)
The paper proposed usage of LMS Moodle for adaptive learning implementation because of its simplicity and its capabilities. LMS Moodle has wide range of features to satisfy many learning styles. Adaptive learning design in this paper recommended blended learning method which involves face-to-face activity and LMS Moodle utilization. In this initial design stage, only five LMS Moodle activities were chosen. The selected activities have met all learning styles requirements.